ANALISIS STRUKTUR MODAL, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA: ANALISIS STRUKTUR MODAL, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Febry Rosady (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2022)
The purpose of this study is to test the capital structure, profitability, and leverage on company value in consumer goods industry sector manufacturing companies listed on the Indonesia stock exchange in 2017-2021. The population that is used as the object of observation is a manufacturing company in the consumer goods industry sector listed on the Indonesian stock exchange for 2017-2021. The determination of the research sample used the purposive sampling method and obtained a sample of 13 manufacturing companies in the consumer goods industry sector. The results showed that the capital structure and profitability have a positive and significant effect on the value of the company. Leverage has a negative and significant effect on the value of the company In this study, there are still many limitations and shortcomings, namely the influence of independent variables on dependent variables is only able to explain 65.8% so it is necessary to add other independent variables